Analisis Kritis terhadap Putusan Mahkamah Konstitusi atas Pengujian Materiil Undang-Undang tentang Kepolisian - Yogeta Yogeta; Suwari Akhmaddhian (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2025)
The purpose of this study is to analyze the regulations for the appointment and dismissal of the Chief of the Republic of Indonesia Police based on Law Number 2 of 2002 concerning the Police and the Decision of the Constitutional Court (MK) Number 147/PUU-XXIII/2025 concerning the material review of Article 11 paragraph (2) of Law Number 2 of 2002 concerning the Republic of Indonesia Police. The research method uses a normative juridical method supported by legal materials relevant to the research theme. The results of the study are that the petition was filed by two applicants, but only Applicant I was declared to have legal standing. The focus of the review relates to the unclear term of office of the Chief of the Republic of Indonesia Police, multiple interpretations of the explanation of the article, and the alleged inconsistency of norms with the principles of the rule of law. The MK's considerations rejected the petition, and analyzed it using Lawrence M. Friedman's Legal System Theory, which includes legal structure, legal substance, and legal culture. The conclusion of the study shows that the Constitutional Court considers the norms of the Police Law to be still constitutional, and the ambiguity argued by the Applicant has been answered through previous Constitutional Court decisions. The Constitutional Court's ruling confirms that, structurally and institutionally, the President's prerogative authority regarding the National Police Chief remains compatible with the principles of the rule of law. While there is still room for improvement in terms of substance and legal culture to strengthen legal certainty.